Analysis of the Effect of Tourism Development on Tourist Satisfaction in the Bukit Indah Simarjarunjung Tourism Area, Pariksabungan Village, Simalungun Regency - Yan Saputra Saragih (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the effect of tourism development in terms of attractions, accessibility, amenities and ancillary services on tourist satisfaction in the Bukit Indah Simarjarunjung Tourism Area, Simalungun Regency. The method used is a survey method using a Likert model questionnaire which is distributed using the Google Form. The sample selection method used simple random sampling with a total of 116 respondents. This study uses descriptive analysis with a quantitative approach with multiple linear regression. Each independent variable (X) is then subjected to a t-test and f-test to the dependent variable (Y). The results show that Ataction, Accessibility, Amenities and Asilari Services have a positive and significant effect both partially and simultaneously on tourist satisfaction in the Bukit Indah Tourism Area Simarjarunjung, Simalungun Regency. From the results of the dominant test, it was found that tourist attractions were the most influential variable on tourist satisfaction. Amenities are the variables that need the most attention to strive for their development.